Endovascular treatment of postpartum haemorrhage in a woman with genitourinary and vascular congenital malformations. Issue 3 (23rd March 2021) - Perkins, Scott; Drews, Elena; Li, Gabriel; Martin, Jonathan
Abstract : A 43-year-old woman presented with postpartum haemorrhage necessitating uterine artery embolisation. Prior to embolisation, angiography demonstrated the presence of a persistent sciatic artery (PSA). Due to the possibility of embolic particles inadvertently traveling to the lower extremity via this variant arterial pathway, care was taken to only embolise the uterine artery. PSAs are uncommon but important vascular pathways to screen for during pelvic intervention and are associated with other genitourinary anomalies.